PELAKSANAAN PERMOHONAN PENDAFTARAN HAK MILIK ATAS TANAH SESUAI DENGAN ASAS KONTRADIKTUR DELIMITASI SESUAI PASAL 17 AYAT 1 PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 DI DESA SUNGAI RAYA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - NIM. A1012161207, MUHAMMAD BAHTIAR TUARITA (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractThe determination of these boundaries is carried out by landowners, and the landowners whose properties are adjacent are known as the principle of contradictory delimitation, which essentially instills the principle of consensus contained in the fourth principle of Pancasila as the foundation for its application in society. The principle of Contradictory Delimitation involves the installation of boundary markers and the determination of boundary points at the corners of the land plots, which are agreed upon by the directly adjacent parties. This principle aims to prevent disputes, conflicts, and land-related issues in the future. However, up until now, the implementation of the principle of contradictory delimitation itself is considered ineffective and seems to be overlooked by the community, especially those who have interests related to land in Indonesia. Therefore, a comprehensive study is needed that can factually prove